Morpho-physiological response to vertically heterogeneous soil salinity of two glycophyte woody taxa, Salix matsudana x S. alba and Eucalyptus camaldulensis Dehnh - Quiñones Martorello, Adriana; Gyenge, Javier; Fernandez, María Elena (Springer International, 2018)
Aims Growth and physiology of Salix matsudana x S. alba and E. camaldulensis were evaluated in vertical saline gradients to test whether growth is determined by the mean salinity of rhizosphere, the average salinity weighed by the root number in each portion of the soil, the lowest or the highest rhizosphere salinity. Methods Saplings were grown in pots with an original irrigation system determining upper and lower soil layers with a combination of 4 treatments: control, moderate homogeneous salinity (Ho), and heterogeneous salinity, with high concentration of NaCl in the upper (HeU) or in the lower soil layer (HeL). Results E. camaldulensis saline treatments decreased Ψpre-dawn and Ψosmotic. HeU and HeL did not decrease stem growth (RVG), but HeL reduced root biomass in lower soil layer. Ho treatment reduced RVG (50%), increasing leaf senescence and altering some ions concentration (but not Na+). In Salix sp., Ho decreased Ψpre-dawn and chlorophyll content, increasing leaf senescence and Cl− concentration resulting in low leaf biomass. HeL also decreased plant total biomass. Conclusions Lower concentration of salt homogeneously distributed in soil profile would have more effect than high salt concentration but restricted to one soil layer. The negative impact of high salinity would be higher if salts are in deeper than in upper soil layers. Salt tolerance thresholds would then depend more on the salt spatial distribution in the soil than on its average concentration along the rhizosphere